2018
DOI: 10.1371/journal.pone.0203143
|View full text |Cite
|
Sign up to set email alerts
|

Development of a broad spectrum glycoconjugate vaccine to prevent wound and disseminated infections with Klebsiella pneumoniae and Pseudomonas aeruginosa

Abstract: Klebsiella pneumoniae (KP) and Pseudomonas aeruginosa (PA) are important human pathogens that are associated with a range of infection types, including wound and disseminated infections. Treatment has been complicated by rising rates of antimicrobial resistance. Immunoprophylactic strategies are not constrained by antimicrobial resistance mechanisms. Vaccines against these organisms would be important public health tools, yet they are not available. KP surface O polysaccharides (OPS) are protective antigens in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 62 publications
0
65
0
Order By: Relevance
“…Pa-derived flagellin was purified and adsorbed with polymyxin B-agarose to remove bacterial LPS, after which less than 0.1 LPS units/g of protein was detected by the Limulus amebocyte lysate assay as described (20). Flagellin was purified from STm strain CVD1925, a derivative of the WT invasive Malian strain I77, as described (79,80). Both Pa and STm flagellins exhibited a single Coomassie Blue-stained protein band following SDS-PAGE.…”
Section: Purification Of Pa and Salmonella Typhimurium Flagellinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pa-derived flagellin was purified and adsorbed with polymyxin B-agarose to remove bacterial LPS, after which less than 0.1 LPS units/g of protein was detected by the Limulus amebocyte lysate assay as described (20). Flagellin was purified from STm strain CVD1925, a derivative of the WT invasive Malian strain I77, as described (79,80). Both Pa and STm flagellins exhibited a single Coomassie Blue-stained protein band following SDS-PAGE.…”
Section: Purification Of Pa and Salmonella Typhimurium Flagellinsmentioning
confidence: 99%
“…Both rFlaA and rFlaB proteins were purified as described (79) and exhibited a single Coomassie Blue-stained protein band following SDS-PAGE. For preparation of mouse polyclonal antisera to rFlaA and rFlaB, 6-to 7-week-old female Crl:CD-1 mice (Charles River Laboratories) were injected in the right gastrocnemius muscle on 0, 14, and 28 days with 2.5 g of rFlaA or rFlaB flagellins, as described (80). Blood was collected by retro-orbital bleeding at 14 days following the final immunization and centrifuged, and the serum stored at Ϫ20°C.…”
Section: Muc1-ed Is a Shed Decoy Receptor In Vivomentioning
confidence: 99%
“…ATCC 43816) that are highly and rapidly lethal in mice (Fodah et al, 2014;Hsieh et al, 2013;Lau et al, 2007;Lavender et al, 2004;Lawlor et al, 2005;Lin et al, 2014;Wu et al, 2009), precluding their utility in illuminating natural adaptive immune responses to live K. pneumoniae. Instead, experiments have assessed adaptive immunity elicited by heat-killed organisms and a variety of specific K. pneumoniae immunogenic factors, including outer membrane vesicles, O-antigens, type 3 fimbriae and purified capsule (Chen et al, 2011;Cryz et al, 1985;Lee et al, 2015;Amezcua Vesely et al, 2019;Lavender et al, 2005;Trautmann et al, 2004;Hegerle et al, 2018). Early work in rodents and subsequently humans indicated that immunization with capsule elicits serotype-specific antibody responses (Cryz et al, 1985;Alcantar-Curiel et al, 1993;Cryz et al, 1988Cryz et al, , 1984Cryz et al, , 1986a; however, capsule is not the sole driver of protective immunity during infection (Lee et al, 2015;Lundberg et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Both P. aeruginosa and K. pneumoniae account for many nosocomial infections that are increasingly complicated to treat due to antibiotic resistance. A glycoconjugate vaccine against K. pneumoniae and P. aeruginosa infections is also in preclinical development; results so far are promising for development of this broad-spectrum human vaccine (Hegerle et al, 2018). The vaccine formulation includes the four predominant surface O polysaccharides associated with K. pneumoniae infection, conjugated to a protein carrier to enhance immunity.…”
Section: New Vaccine Technologies and Targetsmentioning
confidence: 99%
“…Flagellin proteins from P. aeruginosa were selected as carrier proteins in order to produce a vaccine targeting both K. pneumoniae and P. aeruginosa infections. This approach to extend vaccine coverage to other pathogens has only been used in one other vaccine to date, a pneumococcal conjugate vaccine that uses protein D from non-typeable H. influenzae (NTHi) as a carrier (Hegerle et al, 2018).…”
Section: New Vaccine Technologies and Targetsmentioning
confidence: 99%